Perspectives on Mars Sample Return: A critical resource for planetary science and exploration - Harry Y. McSween; Victoria E. Hamilton; Kenneth A. Farley (Proceedings of the National Academy of Sciences, 2025)
Mars Sample Return (MSR) has been the highest flagship mission priority in the last two Planetary Decadal Surveys of the National Academies of Science, Engineering, and Medicine (hereafter, “the National Academies”) and was the highest priority flagship for Mars in the Decadal Survey that preceded them. This inspirational and challenging campaign, like the Apollo program’s returned lunar samples, will potentially revolutionize our understanding of Mars and help inform how other planets are explored. MSR’s technological advances will keep the NASA and European Space Agency at the forefront of planetary exploration, and data on returned samples will fill knowledge gaps for future human exploration. Investigations of the ancient rocks collected in and around Jezero crater, as well as samples of the regolith and atmosphere, will be fundamentally different in scope, depth, and certainty from what is achievable with spaceborne observations. Returned Mars samples can address critical science issues including the discovery and characterization of ancient extraterrestrial life, prebiotic organic chemistry, the history of habitable planetary environments, planetary geological, geochemical, and geophysical evolution, orbital dynamics of bodies in the early Solar System, and the formation and evolution of atmospheres.